iBEX: Modular Open-Source Software for Digital Radiography. - Brusan, Altay; Durmaz, F. Aytaç; Yaman, Alper; Öztürk, Cengizhan (Journal of Digital Imaging, 2020)
A device-independent software package, named iBEX, is developed to accelerate the research and development efforts for X-ray imaging setups such as chest radiography, linear and multidirectional tomography, and dental and skeletal radiography. Its extension mechanism makes the software adaptable for a wide range of digital X-ray imaging hardware combinations and provides capabilities for researchers to develop image processing plug-ins. Independent of the X-ray sensor technology, iBEX could integrate with heterogeneous communication channels of digital detectors. iBEX is a freeware option for preclinical and early clinical testing of radiography devices. It provides tools to calibrate the device, integrate to health information infrastructure, acquire image, store studies on local storage, and send them to Picture Archiving and Communication System (PACS). iBEX is a unique open-source project bringing X-ray imaging devices' software into the scope of the open-source community to reduce the X-ray scanners' research effort, potentially increase the image quality, and cut down the production and testing costs of radiography devices.